Firm size and monetary policy transmission: evidence from German business survey data - Michael Ehrmann (Center for Economic Studies and ifo Institute (CESifo), 2004)
Using business survey data on German manufacturing firms, this paper provides tests for hypotheses formulated in capital market imperfection theories that predict distributional effects in the transmission of monetary policy. The business conditions of small firms are found to be somewhat more sensitive to monetary policy shocks than those of large firms, also when accounting for demand differences. These effects are reinforced in business cycle downturns.
Keywords: E52; E32; C32; 330; monetary policy transmission; firm size; Markov switching; Geldpolitik; Transmissionsmechanismus; Betriebsgröße; Schock; Konjunkturumfrage; Theorie; Deutschland